Intervertebral Disc Progenitors: Lessons Learned from Single-Cell RNA Sequencing and the Role in Intervertebral Disc Regeneration - Yu-Dong Zhao; Yong-Can Huang; Jia-Liang Lin; Wei-Shi Li (Bioengineering, 2023)
The tremendous personal and economic burden worldwide caused by low back pain (LBP) has been surging in recent years. While intervertebral disc degeneration (IVDD) is the leading cause of LBP and vast efforts have been made to develop effective therapies, this problem is far from being resolved, as most treatments, such as painkillers and surgeries, mainly focus on relieving the symptoms rather than reversing the cause of IVDD. However, as stem/progenitor cells possess the potential to regenerate IVD, a deeper understanding of the early development and role of these cells could help to improve the effectiveness of stem/progenitor cell therapy in treating LBP. Single-cell RNA sequencing results provide fresh insights into the heterogeneity and development patterns of IVD progenitors; additionally, we compare mesenchymal stromal cells and IVD progenitors to provide a clearer view of the optimal cell source proposed for IVD regeneration.